2021
DOI: 10.3389/fncel.2020.567253
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of LRP1 From Astrocytes Modifies Neuronal Network Activity in an in vitro Model of the Tripartite Synapse

Abstract: The low-density lipoprotein receptor-related protein 1 (LRP1) is a transmembrane receptor that binds over 40 potential ligands and is involved in processes such as cell differentiation, proliferation, and survival. LRP1 is ubiquitously expressed in the organism and enriched among others in blood vessels, liver, and the central nervous system (CNS). There, it is strongly expressed by neurons, microglia, immature oligodendrocytes, and astrocytes. The constitutive LRP1 knockout leads to embryonic lethality. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…Furthermore, we noted a downregulation of Lrp1, an important modulator of the ECM [75]. Interestingly, deletion of Lrp1 from astrocytes in a hippocampal neuron co-culture model decreased neuronal network activity and influenced the proportion of pre-and postsynaptic structures [76]. In summary, we noted an extensive ECM remodeling and severe synaptic imbalance in quadruple mutant mice, which contribute to the impaired visual function and optomotor behavior.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, we noted a downregulation of Lrp1, an important modulator of the ECM [75]. Interestingly, deletion of Lrp1 from astrocytes in a hippocampal neuron co-culture model decreased neuronal network activity and influenced the proportion of pre-and postsynaptic structures [76]. In summary, we noted an extensive ECM remodeling and severe synaptic imbalance in quadruple mutant mice, which contribute to the impaired visual function and optomotor behavior.…”
Section: Discussionmentioning
confidence: 57%
“… 79 Interestingly, deletion of Lrp1 from astrocytes in a hippocampal neuron co-culture model decreased neuronal network activity and influenced the proportion of pre- and postsynaptic structures. 80 In summary, we noted an extensive ECM remodeling and synaptic imbalance in quadruple mutant mice, which contribute to the impaired visual function and optomotor behavior.…”
Section: Discussionmentioning
confidence: 71%
“…Alternatively, blocking endocytosis could cause Aβ to remain bound at the cell membrane (for example through binding to a receptor such as LRP1) for a prolonged period of time, which could have subsequent effects on intracellular signalling. Interestingly, differential levels of cytokines are observed in culture medium from neurons co-cultured with either wild type or LRP1-deficient astrocytes (Romeo et al, 2021), which suggests that LRP1 signalling in astrocytes may affect cytokine release. This is supported by another study, which found that LRP1 mediates Aβ-induced astrocyte activation, including the increased expression of the cytokine IL-1β (LaDu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%